2006
DOI: 10.1111/j.1365-3040.2006.01536.x
|View full text |Cite
|
Sign up to set email alerts
|

Guard cells in albino leaf patches do not respond to photosynthetically active radiation, but are sensitive to blue light, CO2 and abscisic acid

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 65 publications
4
90
0
Order By: Relevance
“…Stomatal responses to light have been characterized in angiosperms such as Arabidopsis, C. communis, and V. faba (Zeiger, 1983;Assmann, 1993;Willmer and Fricker, 1996;Roelfsema et al, 2006;Shimazaki et al, 2007). In these plants, stomatal opening is mediated by two light signaling cascades, BL-dependent and photosynthesis-induced responses (Shimazaki et al, 2007;Kollist et al, 2014;Lawson et al, 2014).…”
Section: Discussion Bl Response Of Stomata Is Present In Early Vasculmentioning
confidence: 99%
See 1 more Smart Citation
“…Stomatal responses to light have been characterized in angiosperms such as Arabidopsis, C. communis, and V. faba (Zeiger, 1983;Assmann, 1993;Willmer and Fricker, 1996;Roelfsema et al, 2006;Shimazaki et al, 2007). In these plants, stomatal opening is mediated by two light signaling cascades, BL-dependent and photosynthesis-induced responses (Shimazaki et al, 2007;Kollist et al, 2014;Lawson et al, 2014).…”
Section: Discussion Bl Response Of Stomata Is Present In Early Vasculmentioning
confidence: 99%
“…Both mesophyll and guard cells possess photosynthetically active chloroplasts, and their photosynthesis has been suggested to contribute to stomatal opening in leaves. The decrease in the concentration of intercellular CO 2 (Ci) caused by photosynthetic CO 2 fixation or some unidentified mediators and metabolites from mesophyll cells is supposed to elicit stomatal opening, although the exact nature of the events is unclear (Wong et al, 1979;Vavasseur and Raghavendra, 2005;Roelfsema et al, 2006;Mott et al, 2008;Lawson et al, 2014).…”
mentioning
confidence: 99%
“…87 For example, it has been shown that chloroplast-containing guard cells in albino sections of variegated leaves do not respond to photosynthetically active radiation, but are sensitive to blue light and CO 2 , bringing into question a direct role of guard cell photosynthesis on red-lightmediated stomatal opening in intact leaves. 35 …”
Section: Aba Sensing and Signalingmentioning
confidence: 99%
“…Potentially, CO 2 could be directly sensed by the guard cells 22,35 or remotely via communication from the mesophyll cells. 15,36,37 It is additionally possible that both cells types could be directly involved in the stomatal CO 2 response.…”
Section: Co 2 and Stomatal Developmentmentioning
confidence: 99%
“…It should be noted that the spider plants had variegated white and green leaves with a white strip down the middle of each leaf blade. Research has shown that stomata in white portions of leaves do not respond to photosynthetically active radiation (Roelfsema et al, 2006). Total leaf area was reported in the results, but the effective spider plant leaf area for photosynthesis was less than the reported total area.…”
Section: Estimated T R a N S P I R A T I O N Fluxesmentioning
confidence: 56%